Lactoferrin-chia seed mucilage complex coacervates for intestinal delivery of quercetin and fortification of set yogurt - Shishir, Mohammad Rezaul Islam; Suo, Hao; Taip, Farah Saleena; Cheng, Ka Wing (Elsevier Ltd, 2024)
This study aimed to develop complex coacervates utilizing lactoferrin (LF) and chia seed mucilage (CSM) for promoting intestinal delivery of quercetin (Q) and fortification of set yogurt. Three cross-linkers, including calcium chloride (CC), transglutaminase (TG), and polyphenolic complex (HP), were used to further reinforce the coacervate network. Cross-linked coacervates had higher values of coacervate yield, encapsulation efficiency, and loading capacity. They efficiently preserved Q under gastric condition (⁓87%–99%), with CSM-TG-Q-LF being most effective for intestinal delivery of Q. Moreover, digested pellets of the cross-linked coacervates displayed better antioxidant activity than the uncross-linked coacervates with CSM-TG-Q-LF pellets showing maximum bioactivity. The Q-loaded coacervates demonstrated superior assembly in the yogurt matrix compared to the unencapsulated Q. Moreover, the coacervate systems, especially CSM-TG-Q-LF significantly improved the textural properties of yogurt and the stability of Q in it. Therefore, CSM-TG-LF is a promising carrier to promote intestinal delivery and food application of hydrophobic molecules.